The role of BRCA1 mutations and G/C polymorphism of RAD51 in breast cancer - Romanowicz-Makowska, Hanna; Sobczuk, Anna; Smolarz, Beata; Zadrożny, Marek; Westfal, Bogusław; Stetkiewicz, Tomasz; Kulig, Andrzej (Menopause Review/Przegląd Menopauzalny, 2005)
Aim: In present work the frequency of BRCA1 germ-line mutations and the RAD51 G/C polymorphism in patients with breast cancer was investigated. Methods: Blood was obtained from 50 breast cancer women. Blood samples age matched healthy individuals (n = 46) served as control. The G/C polymorphism and BRCA1 mutations were determined by PCR-RFLP methods. Results: The distribution of the genotypes of the G/C polymorphism RAD51 in both control and patients did not differ significantly (P >0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences in the genotype distributions and allele frequencies between node-positive and node-negative patients. In present study one Ex20insC mutations of BRCA1 gene was identified in women with breast cancer. Conclusion: Our study implies that the G/C polymorphism of the RAD51 gene may not be directly involved in the development and/or progression of breast cancer. The lack of detectable BRCA1 germ-line mutations in most cases suggests that there are probably additional, as yet unidentified genes predisposing to this disease.